OPTIMIZATION OF WAREHOUSE FUNCTIONS, GOOD RECEIVING AND GOODS RETURN PROCEDURES : study case: Assalam Hypermarket - astrid noviana paradhita; Yohanes Wien Tineka (This journal is published by the Vocational School of Universitas Sebelas Maret., 2024)
Warehouses have an essential role in the sustainability of retail businesses. A warehouse is not only a place to store goods but also receives, distributes, and returns goods. Assalam Hypermarket is a retail business that still needs help maximizing warehouse functions. Assalam Hypermarket still has several obstacles that could be solved, such as fighting over goods between warehouse divisions, damage to goods, and distribution delays. This research aims to analyze the causes of problems and optimize the implementation of warehouse functions. This research was conducted by applying qualitative descriptive research methods to analyze the function of the warehouse at the Assalam Hypermarket shopping center. The research flow is carried out systematically, from determining the research design, determining research objects and subjects, collecting data and information, analyzing data and information, drawing conclusions, and providing solution recommendations. From this research, results were obtained in the form of factors that cause problems in carrying out warehouse functions. Therefore, Assalam Hypermarket can continue to provide regular outreach regarding SOPs for receiving and returning goods to warehouse staff. Assalam Hypermarket can also print SOPs for receiving and returning goods at the warehouse and implement a cross-decking model to run warehouse operations. Apart from that, Assalam Hypermarket can also improve the competency of warehouse staff by providing BIT training.